Anxiety, Depression, and Post-Traumatic Stress Disorders in Pediatric Oncology Patients and Their Mothers - Ezgi Özlem Özmen; Arzu Okur; Esra Güney; Esin Gökçe Sarıpınar; Faruk Güçlü Pınarlı (Gazi Medical Journal, 2025)
Objective: This prospective study aims to investigate the prevalence of anxiety, depression, and post-traumatic stress disorder (PTSD) in pediatric oncology patients and their mothers. Methods: All patients (n=61) aged 8-18 years who were actively treated patients (ATP) and patients in remission (ReP) and their mothers (n=61) were recruited as the study group. The first control group for anxiety and depression consisted of healthy mothers and children (n=60). In contrast, the second control group for PTSD consisted of mothers and children who had experienced non-disease trauma, such as divorce, death of a parent, and loss of income (n=30). The questionnaires were administered to the children and mothers. Results: There was no significant difference between ATP and ReP in depression, anxiety, or PTSD (p=0.35, p=0.56, p=0.20). The children of the patient group were significantly more depressed and anxious than the healthy controls (HCs) (p=0.001, p=0.005). ATP mothers were more anxious than ReP mothers (p=0.004), but there was no difference in depression and burnout between the two groups (p=0.09, p=0.526). Mothers in the patient group were more anxious and depressed than mothers in the HC (p<0.001). The patient group and their mothers showed more PTSD symptoms compared to the HCs with trauma (p<0.05). Conclusion: Pediatric cancer is a significant stressor for both children and mothers. A combination of medical treatment with psychosocial support is imperative.